Structure and property study for heterobimetallic Au Ag and Au Cu thiolate interlocked [2]catenane and comparison with homometallic Au Au gold() thiolate interlocked [2]catenanes - a theoretical study - Liu, Yang; Wu, Shui-xing; Pan, Qing-qing; Gao, Feng-wei; Duan, Ying-chen; Kan, Yu-he; Su, Zhong-min (New journal of chemistry, 2024)
A series of heterobimetallic (Au Ag interlocking and Au Cu interlocking) [2]catenanes were studied using DFT and TD-DFT methods to explore the relationship between their structures and properties. In order to fully investigate the influence of metal type in these [2]catenanes and compare the similarities and differences between these heterobimetallic and homometallic catenanes, the results were also compared with our previously studied homometallic Au Au interlocking [2]catenane molecules. The results display that the steric hindrance increases with the increase of the number of monomers, and thus the distances between the center and the edge of the rings become longer, demonstrating a trend of outward expansion. As the size of the ring becomes larger, the total weak interaction increases and shows increasingly dispersed distribution. The value of the dispersion interaction energy increases with the overgrowth of the size of molecular systems and correspondingly the energy level of the frontier orbital decreases and the energy gap becomes bigger when two hexamers interlock. Compared with the Au Ag interlocking [2]catenanes, the Au Cu interlocking [2]catenanes present red-shifted absorption spectra, which is consistent with their smaller energy gap. The hole-electron analysis results indicate that the S 0 → S 1 excitations are almost unidirectional charge transfer excitations due to the significant separation of holes and electrons, while for the high-energy excited states, local excitations occupy a dominant position. Through the study of the specific proportion of charge transfer on each fragment in the main transition process, we found that for heterometallic [2]catenanes, the Cu atom in the Au Cu interlocking [2]catenanes has a greater influence on the electronic structure. As for homometallic [2]catenanes, the effects of Au atoms in the two rings are equivalent on the electronic structure. To explore the difference of Au Ag/Cu and Au Au interlocking thiolate [2]catenanes, we carried the comparison of the geometric and electronic structures, ultraviolet-visible spectra and composition of intermolecular interaction forces theoretically.